2015
DOI: 10.1080/10942912.2014.968284
|View full text |Cite
|
Sign up to set email alerts
|

Oil Content and Fatty Acids Composition inBrassicaSpecies

Abstract: Seeds of 20 accessions of six Brassica species including cultivated and five wild relatives were analyzed for oil and fatty acid composition. The Results showed that oil content varied from 21 (B. nigra) to 46% (B. napus). Among wild species, B. rapa and B. oleracea had highest oil content (31 and 28 %, respectively). The main fatty acids of oleic, linoleic, linolenic, erucic,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
70
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 17 publications
(18 reference statements)
22
70
1
Order By: Relevance
“…Most of the changes described here are explained by the unique FA profile that brassicas have. In this study, the FA profile from diets (Table 1) showed that brassicas have high contents of FA with >20 carbons, which is in agreement with previous research on different brassica species (Sharafi et al, 2015).…”
Section: Resultssupporting
confidence: 92%
“…Most of the changes described here are explained by the unique FA profile that brassicas have. In this study, the FA profile from diets (Table 1) showed that brassicas have high contents of FA with >20 carbons, which is in agreement with previous research on different brassica species (Sharafi et al, 2015).…”
Section: Resultssupporting
confidence: 92%
“…). Seeds such as cruciferous mustard ( Brassica juncea ), radish ( Raphanus sativus ), Chinese cabbage ( Brassica campestris ), white flax ( Camelina sativa ), rapeseed ( Brassica napus ), meadowfoam ( Limnanthes alba ), rocket grass ( Eruca sativa ), and nasturtium ( Nastrutium officinale ) contain large amounts of C 20 or longer chain unsaturated fatty acids (Table ). Mustard seed oil contains more than 40% erucic acid (C22:1, ω ‐9), which can produce 1‐decene and 13‐tetradecenoic acid.…”
Section: Bio‐oil Type and Compositionmentioning
confidence: 99%
“…Unlike Canola, its ancestral cauliflower and turnip seed oil contains more than 40% erucic acid. Black mustard ( Brassica nigra ), Brassica juncea (a hybrid of black mustard and turnip), and Brassica carinata (a hybrid of black mustard and cauliflower) also contain a large amount of erucic acid . On the other hand, breeding studies were carried out to increase the content of erucic acid as the value for industrial applications, such as the raw materials for polymer production, increased, and a 72% lecithin variety was developed .…”
Section: Bio‐oil Type and Compositionmentioning
confidence: 99%
“…In general, rapeseed oil contains ∼7% saturated fatty acids (including palmitic acid and stearic acid), and high amounts of monounsaturated fatty acids with a significant fraction of oleic acid (∼61%). It also contains an important amount of polyunsaturated fatty acids with significant fraction of linoleic acid (∼11%) and a-linolenic acid (∼21%) (Sharafi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%